Methotrexate persistence and adverse drug reactions in patients with juvenile idiopathic arthritis. (8th March 2019) - Kearsley-Fleet, Lianne; Vicente González, Laura; Steinke, Douglas; Davies, Rebecca; De Cock, Diederik; Baildam, Eileen; Beresford, Michael W; Foster, Helen E; Southwood, Taunton R; Thomson, Wendy; Hyrich, Kimme L
Abstract: Objectives: This analysis aims to calculate MTX monotherapy persistence and describe the occurrence of and factors associated with the occurrence of adverse drug reactions (ADRs) with MTX. Methods: Patients with JIA starting MTX monotherapy from two UK studies were included. Patient characteristics, treatment details and ADR occurrence were collected at treatment start, 6 months, 1 year and annually. The following groups of ADRs were included: gastrointestinal, elevated liver enzymes, leukopenia, drug hypersensitivity, rash, needle phobia and any events leading to permanent MTX discontinuation. Treatment exposure was calculated from MTX start until MTX monotherapy cessation, last follow-up or 31 December 2017 (cut-off), whichever came first. Survival analysis assessed the time on MTX monotherapy and the time to the first ADR on MTX monotherapy within 2 years. Multivariable logistic regression assessed characteristics associated with any ADR and gastrointestinal ADRs. Results: A total of 577 patients started MTX. At 2 years, 310 (54%) were no longer on MTX monotherapy. Reasons included ineffectiveness (60%; 161/185 started a biologic), adverse event (25%), remission (8%) and patient/family decision (3%). Over this time, 212 (37%) patients experienced one or more ADR; commonly gastrointestinal (68%) or elevated liver enzymes (26%). Lower physician global assessment and older age predicted any ADR and gastrointestinal ADR, respectively. Patients with polyarticular RF and JIA had reduced odds of both any ADR and a gastrointestinal ADR. Conclusion: After 2 years, more than half the patients were no longer on MTX monotherapy, while more than one-third experienced one or more ADR, most commonly gastrointestinal. Research focusing on identifying which children will respond and/or experience ADRs is crucial to inform treatment decisions and management planning.